2015
DOI: 10.1007/s00261-015-0539-0
|View full text |Cite
|
Sign up to set email alerts
|

T1-hyperintense renal lesions: can high signal predict lack of enhancement?

Abstract: Signal ratio of lesion to cortex ≥ 2.15 on unenhanced T1-weighted images is a highly specific predictor for non-enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Specifically, papillary renal cell carcinoma has a propensity to show intralesional hemorrhage [18,23], and accounted for 57% of our malignant masses, despite only representing 10-15% of all renal cell carcinoma [24]. Prior studies examining T1-hyperintense renal lesions similarly reported enriched proportions of papillary renal cell carcinoma, ranging from 32% to 46% [25,26]. Furthermore, studies focusing on papillary renal cell carcinomas showed high frequencies of T1 hyperintensity [27,28].…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, papillary renal cell carcinoma has a propensity to show intralesional hemorrhage [18,23], and accounted for 57% of our malignant masses, despite only representing 10-15% of all renal cell carcinoma [24]. Prior studies examining T1-hyperintense renal lesions similarly reported enriched proportions of papillary renal cell carcinoma, ranging from 32% to 46% [25,26]. Furthermore, studies focusing on papillary renal cell carcinomas showed high frequencies of T1 hyperintensity [27,28].…”
Section: Discussionmentioning
confidence: 97%